2020
DOI: 10.1590/1806-9061-2019-1083
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Perch Cooling on Behavior, Welfare Criteria, Performance, and Litter Quality of Broilers Reared at High Temperatures with Different Litter Thicknesses

Abstract: The first aim of this study was to investigate the effects of perch cooling and different litter thicknesses on litter quality of the housing facility, welfare criteria (incidence of footpad and hock burns, gait score, plumage cleanliness and damages), heterophil/lymphocyte ratio, growth, and carcass compositions of broilers reared at high ambient temperature. Secondly, the study was conducted to determine whether cooled perches would be preferred by broiler chickens exposed to a hot environment, and subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…In the present investigation, the bedding had the same thickness in all treatments (approximately 15 cm). Fidan et al (2020) state that bedding with this thickness leads to a reduction in atmospheric ammonia, which may have contributed to the low values found in the present study. Eliotts & Collins (1982) found that an increase in bedding moisture led to a reduction in NH 3 in the first week of rearing broiler chickens, but the opposite occurred in the subsequent weeks.…”
Section: Influence Of Ammonia Gas On Histomorphometry and Histopathol...contrasting
confidence: 55%
“…In the present investigation, the bedding had the same thickness in all treatments (approximately 15 cm). Fidan et al (2020) state that bedding with this thickness leads to a reduction in atmospheric ammonia, which may have contributed to the low values found in the present study. Eliotts & Collins (1982) found that an increase in bedding moisture led to a reduction in NH 3 in the first week of rearing broiler chickens, but the opposite occurred in the subsequent weeks.…”
Section: Influence Of Ammonia Gas On Histomorphometry and Histopathol...contrasting
confidence: 55%
“…Wu and Hocking [14] also found that wet litter (more than 30% moisture) leads to impaired footpad condition. Moreover, wet litter conditions lead to deterioration in plumage cleanliness [15], broiler growth, and feed efficacy [10].…”
Section: Introductionmentioning
confidence: 99%
“…BimonthlyThe publications were selected by affinity or connection with the relative field, such as, for example, the article "The Effects of Perch Cooling on Behavior, Welfare Criteria, Performance, and Litter Quality of Broilers Reared at High Temperatures with Different Litter"40 , published in the Brazilian Journal of Poultry Science.…”
mentioning
confidence: 99%